Investigation of non-cholinergic acetylcholinesterase, and related peptides in an in vitro preparation of the substantia nigra - Whyte, K; Whyte, Kathryn Antonia (2001)
﻿ The primary role of acetylcholinesterase (AChE) is hydrolysis of acetylcholine (ACh). However, observations by numerous groups have suggested that AChE may have non-cholinergic functions. Furthermore, developmental roles for AChE and its related enzyme, butyrylcholinesterase (BuChE), which is also capable of ACh hydrolysis, have been postulated. One line of evidence to support a non-cholinergic role for AChE is the apparent disparity in several brain areas between the distribution of AChE and the cholinergic marker choline acetyltransferase. The substantia nigra (SN), an area of the ventral mesencephalon (VM), which contains the dopaminergic cells that degenerate in Parkinson's disease (PD), is an area that displays such a disparity. One approach to treating PD involves implantation of embryonic dopaminergic VM cells into the parkinsonian brain. This procedure, known as foetal transplantation, has met with limited success, in part due to degeneration of dopaminergic cells within the donor preparation. It is known that incorporation of trophic factors into the preparation for grafting improves dopaminergic cell survival. It has previously been shown that AChE enhances survival and neurite outgrowth of postnatal dopaminergic cells in organotypic cultures of the VM. The aim of the studies in this thesis was to establish the effects of BuChE and AChE on embryonic dopaminergic neurons in a preparation analogous to that used in the animal model of foetal transplantation as a treatment for PD. Addition of BuChE and monomeric (G1-) and tetrameric (G4-) forms of AChE enhanced dopaminergic neurite outgrowth. Inhibition of the active site of BuChE and AChE by echothiophate had no effect upon neurite outgrowth or cell survival, demonstrating that the trophic effects of BuChE and AChE on neurite outgrowth were not dependent upon ACh hydrolysis. In contrast, inhibition of the peripheral anionic site (PAS) of AChE by BW284c51 markedly decreased cell survival and neurite outgrowth. The mechanism of action of BW284c51 toxicity was subsequently investigated using a mixture of nicotinic ACh receptor antagonists in order to demonstrate that the chronic toxic effects of BW284c51 were not a consequence of elevated ACh resulting from inhibition of AChE. Finally, the technique of whole-cell patch-clamp electrophysiology revealed a novel inhibitory effect of BuChE and G1- and G4-AChE on voltage-dependent calcium currents. It was postulated that these actions underlie the trophic effects of BuChE and AChE on embryonic dopaminergic neurons, a suggestion that was supported by the findings that established inhibitors of voltage-dependent calcium currents enhanced dopaminergic neurite outgrowth. The findings of this thesis are discussed in the context of other studies and are related to both physiological and pathological functions of the central nervous system.